Edukasi Upaya Pencegahan Gangguan Kesehatan Mata di SD Negeri Pancur, Kota Serang, Banten - Muhammad Alyf Romadon; Alvinarose Febri Hardiwijaya; Wulan Shaumi Fadhilati; Yusep Gunawan; Mila Ermila Hendriyani (IHSAN : JURNAL PENGABDIAN MASYARAKAT, 2023)
Education in efforts to prevent eye health problems as a form of community service. The socialization was carried out at SDN Pancur, Serang City with the theme "Me and My Eye Health" which aims to provide knowledge and information about how to maintain and care for eye health. Education was given to Class 4 5 students which was attended by 70 students. Data collection techniques were carried out by means of a questionnaire with 10 question items. This research method uses lectures and discussions. Data collection techniques were carried out by means of observation and questionnaires with 10 items. The results of this study were 22.9% of students did not know how to maintain eye health and 48.6% of students had bad habits that could reduce the quality of vision. Prevention of damage to the eyes can be done by avoiding bad habits, eating nutritious foods, and getting used to caring for them. eye health.